2013
DOI: 10.1089/gtmb.2012.0383
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Genetic Variants of DNA Repair Genes and Coronary Artery Disease

Abstract: Polymorphisms in DNA repair genes may be associated with differences in the repair efficiency of DNA damage and may influence an individual's risk of atherosclerosis. Genetic research on coronary artery disease (CAD) has traditionally focused on investigation aimed at identifying disease-susceptibility genes. The aim of this study was to investigate the relationship between AP-endonuclease-1 (Asp148Glu), XRCC1 (Arg399Gln), XRCC3 (Thr241Met), XPD (Lys751Gln), XPG (Asp1104His), and hOGG1 (Ser326Cys), gene polymo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 29 publications
1
20
3
Order By: Relevance
“…individuals carrying the variant allele of XRCC1 rs25487 (Arg/Gln or Gln/Gln) [44]. Moreover, while we found no association between OGG1 rs1052133 variants and risk of MI, another study found an increased risk of acute coronary syndrome in carriers of the variant Cys allele [41]. However, the same study showed no association between OGG1 rs1052133 and chronic CAD, which complicates the interpretation of their results [41].…”
Section: Geno Typecontrasting
confidence: 71%
See 3 more Smart Citations
“…individuals carrying the variant allele of XRCC1 rs25487 (Arg/Gln or Gln/Gln) [44]. Moreover, while we found no association between OGG1 rs1052133 variants and risk of MI, another study found an increased risk of acute coronary syndrome in carriers of the variant Cys allele [41]. However, the same study showed no association between OGG1 rs1052133 and chronic CAD, which complicates the interpretation of their results [41].…”
Section: Geno Typecontrasting
confidence: 71%
“…However, we believe that our findings could encourage others to include NEIL3 rs12645561 in their study populations. Notably, we could not find an association of OGG1 rs1052133 with MI, which has been associated with MI in other studies [41]. Thus, replication of SNP association studies is important to draw conclusions about a specific SNP -phenotype association.…”
Section: Snpscontrasting
confidence: 67%
See 2 more Smart Citations
“…On the other hand, one of the polymorphisms found in the XRCC3 gene is characterized by a non-conservative substitution of the amino acid Thr for Met in codon 241 (exon 7). This polymorphism has been studied regarding its influence on the sensitivity to radiation and induction of DNA damage (Gokkusu et al, 2013). The objective of this study was to evaluate the association between the frequency of the XPD-Lys751Gln (rs13181) and XRCC3-Thr241Met (rs861539) polymorphisms and the clinical-pathological profile of a series of OSCC cases.…”
Section: Introductionmentioning
confidence: 99%